How the Iranian Football Coaches and Players Know About Doping? - Seif Barghi, Tohid (Asian J Sports Med, 2015)
BACKGROUND: Nowadays, doping is an intricate dilemma. Football is the nationally popular sport in Iran. On the other hand, doping is a serious health hazard sport faces today. Studies dealing with athletes’ knowledge, attitudes and behavior concerning doping in football are scarce. OBJECTIVES: Therefore, we aimed to investigate the knowledge and attitudes toward doping among the football coaches and players. PATIENTS AND METHODS: In a cross sectional study, 375 participants (239 football players and 136 coaches) were studied. A specially made questionnaire was applied. In this study, football teams of different provinces of the country were selected by randomized clustered sampling and questionnaires were distributed among coaches and players. RESULTS: Knowledge of football coaches and players in three categories of doping definitions, recognition of prohibited drugs and side effects of anabolic steroids was poor or moderate in 45.3%, 88.5% and 96.5%, respectively. CONCLUSIONS: Football players and coaches have poor knowledge about doping in Iran. Moreover, they believe in some inappropriate myths without any scientific or rational basis.It seems necessary to design a comprehensive educational program for all of the athletes and coaches in Iran.